Biological treatment of high strength wastewaters using attached biomass films - Tay, Joo Hwa (2008)
The purpose of the study was to investigate aspects of the use of the Rotating Biological Contactor (RBC) to treat high strength wastewater in a tropical climate. Total organic carbon (TOC), BOD and COD were used as analytical parameters to determine the efficiency of treatment of the wastewater. Also in this study, the fractional removal efficiency and applied - removed loading relationships of the system were compared with predictions from other models.